Chronic Obstructive Pulmonary Disease and Lung Cancer Mortality Attributed to Air Pollution in Türkiye in 2019 - Didem Han Yekdeş; Ali Cem Yekdeş; Ülfiye Çelikkalp; Pelin Sarı Serin; Miraç Çağlayan; Galip Ekuklu (Aerosol and Air Quality Research)
Abstract Approximately seven million premature deaths occurred due to several health problems caused by air pollution. In this study, we aimed to calculate the mortality rates of lung cancer and Chronic Obstructive Pulmonary Disease (COPD) attributed to PM2.5 in Türkiye in 2019. The universe of the research consists of the entire Türkiye region. Air quality data was obtained from the official website of the Ministry of Environment, Urbanization and Climate Change of the Republic of Türkiye. Lung cancer and COPD mortality data were collected from the official website of the Turkish Statistical Institute by a special request. Mortality rates attributed to PM2.5 were calculated with the WHO AIRQ+ program, and the monthly percent change (MPC) in air pollution level was computed by the JP regression method. The annual average values of PM2.5 and PM10 for 2019 in Türkiye were calculated to be 28.82 µg m−3 and 48.08 µg m−3, respectively. The mortality rate attributed to PM2.5 for lung cancer is 15% whereas the mortality rate attributed to PM2.5 for COPD is 22%. Except two Nomenclature d’Unités Territoriales Statistiques (NUTS) regions (TR1, TR7) all other regions have statistically significant one joinpoint. As a conclusion, the PM2.5 average values for 2019 in Türkiye are over the limits for both the national legislation and the World Health Organization (WHO). Taking precautions to control air pollution sources and determination of legitimate national PM2.5 limits should be prioritized. Thus, one out of every six deaths from lung cancer and one out of every five deaths from COPD can be prevented.